Interdisciplinary methodological approach to the process of brownfield revitalisation of traditional industrial areas - Lorber, Lučka (Journal for Geography, 2011)
Traditional industrial regions in the South-East Europe (SEE) represent an underexplored economic value. Revitalisation is delayed and hindered because of legal, financial, environmental and image problems. This weakens competitive investment position for cities and for SEE as a European region. This paper aims at presenting interdisciplinary methodological approach used in a brownfield revitalisation research project. The research work methodology applies the endogenous approach (“bottom up”) on a basis of newly defined land use category of brownfields by the local community. Geography science enjoys an advantage of complexity of understanding spatial issues. This enables geographers to coordinate and harmonize interests between the owners, stakeholders, legislation and human resources. In addition to geographical areas (economic, traffic, demographic, environmental and regional geography) directly involved in the project applicative research, this also includes collaboration of architects, lawyers and economists. The form of applicative research work presented is being developed within the international Revitalisation of Traditional Industrial Areas in South-East Europe (ReTInA) project.  The project is funded in the context of the SEE European Transnational Cooperation Programme 2009/12, involving ten partners from seven countries. The main result of the project will be the new methodology and tools to boost brownfield revitalisation in the municipalities and in old industrial areas of SEE region.
Keywords: applied geography; interdisciplinary methodological approach; endogenous approach; practice tools; brownfield revitalisation